The Influence of Service Quality, Price and Cleanliness to Consumer Satisfaction at Solaria RestaurantManado Town Square 3 - Komaling, Megawati; Lapian, Joyce; Worang , Frederik G. (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
This study aims to test and analyze: The influence of service quality, price and cleanliness simultaneously on consumer satisfaction at Solaria Manado Town Square 3, and. The influence of service quality, price and cleanliness partially on consumer satisfaction at Solaria Manado Town Square. This study uses a survey method and the data collection process is carried out by distributing questionnaires to consumers at Solaria Manado Town Square 3. The sampling technique uses Probability sampling, with a sample size of 150 respondents. The data analysis technique uses multiple linear regression. The results of the study indicate that: There is a positive and significant influence of service quality, price and location on consumer satisfaction at Solaria Manado Town Square 3, the next result is that there is an influence of service quality on consumer satisfaction at Solaria Manado Town Square 3, the next result is that there is an influence of price on consumer satisfaction at Solaria Manado Town Square 3, and the last result is that there is an influence of cleanliness on consumer satisfaction at Solaria Manado Town Square 3.